Evidence-Based Recommendations for Short- and Long-Term Management of Uninvestigated Dyspepsia in Primary Care: An Update of the Canadian Dyspepsia Working Group (CanDys) Clinical Management Tool. (1st May 2005) - van Zanten, Sander JO Veldhuyzen; Bradette, Marc; Chiba, Naoki; Armstrong, David; Barkun, Alan; Flook, Nigel; Thomson, Alan; Bursey, Ford
Abstract : The present paper is an update to and extension of the previous systematic review on the primary care management of patients with uninvestigated dyspepsia (UD). The original publication of the clinical management tool focused on the initial four- to eight-week assessment of UD. This update is based on new data from systematic reviews and clinical trials relevant to UD. There is now direct clinical evidence supporting a test-and-treat approach in patients with nondominant heartburn dyspepsia symptoms, and head-to-head comparisons show that use of a proton pump inhibitor is superior to the use of H2 -receptor antagonists (H2 RAs) in the initial treatment of Helicobacter pylori-negative dyspepsia patients. Cisapride is no longer available as a treatment option and evidence for other prokinetic agents is lacking. In patients with long-standing heartburn-dominant (ie, gastroesophageal reflux disease) and nonheartburn-dominant dyspepsia, a once-in-a-lifetime endoscopy is recommended. Endoscopy should also be considered in patients with new-onset dyspepsia that develops after the age of 50 years. Conventional nonsteroidal anti-inflammatory drugs, acetylsalicylic acid and cyclooxygenase-2-selective inhibitors can all cause dyspepsia. If their use cannot be discontinued, cotherapy with either a proton pump inhibitor, misoprostol or high-dose H2 RAs is recommended, although the evidence is based on ulcer data and not dyspepsia data. In patients with nonheartburn-dominant dyspepsia, noninvasive testing for H pylori should be performed and treatment given if positive. When starting nonsteroidal anti-inflammatory drugs for a prolonged course, testing and treatment with H2 RAs are advised if patients have a history of previous ulcers or ulcer bleeding.